2020
DOI: 10.1111/jce.14485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of touch‐up ablation rate and pulmonary vein isolation durability between hot balloon and cryoballoon

Abstract: Introduction: This study aimed to compare touch-up ablation (TUA) rates and pulmonary vein isolation (PVI) durability of hot balloon ablation (HBA) and cryoballoon ablation (CBA) in paroxysmal atrial fibrillation (PAF) patients.Methods: In total, 137 PAF patients were enrolled in the study. Among them, 59 underwent two HBA procedures at 6-month intervals and 78 patients underwent two CBA sessions, both regardless of atrial fibrillation recurrence. Propensity score matching was performed to estimate similar pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Among the PVI procedures, the anterior ridge and carina area of the LSPV is the thickest area, which profoundly cuts down the energy penetration depth, hinders the creation of a transmural lesion, and concentrates more PV reconnections ( 20 ). Hojo et al reported that a balloon temperature of 70–73°C could reduce TUAs, thereby improving the outcomes ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the PVI procedures, the anterior ridge and carina area of the LSPV is the thickest area, which profoundly cuts down the energy penetration depth, hinders the creation of a transmural lesion, and concentrates more PV reconnections ( 20 ). Hojo et al reported that a balloon temperature of 70–73°C could reduce TUAs, thereby improving the outcomes ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a high balloon temperature setting has been reported to improve the Hotballoon catheter's success rate at the LSPV, additional RF touch-up is recommended to avoid severe PV stenosis, especially in the introduction period. 12 Despite the fact that RF touch-up was frequently required, the Hotballoon catheter was very effective in the long term (Figure 3).…”
Section: Hotballoonmentioning
confidence: 99%
“…With a conventional HB, we set the target internal balloon temperature of 70 °C or 73 °C maintained by delivery of RF current into the balloon to stir the fluid inside for 2–3 min for each PV. There was no information available from the conventional balloon, and the only way to confirm whether the ablation was effective was the pulmonary venous potential obtained from the circular mapping catheter [15] . However, the intra-tube temperature sensor, which is a new sensor, allows us to observe the balloon surface temperature, thereby increasing the information we can obtain.…”
Section: Discussionmentioning
confidence: 99%